2013
DOI: 10.1016/j.spinee.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical results and quality of life after surgical reconstruction for rheumatoid cervical spine

Abstract: Background Context: The EuroQol (EQ-5D) is a widely used comprehensive measure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…After full-text scrutiny with inclusion and exclusion criteria, 37 studies were selected for qualitative synthesis. [22][23][24] As 4 studies did not provide SDs for EQ-5D scores 43,44,64,67 and 2 studies did not provide the EQ-5D score, 46,66 the meta-analysis was performed with 31 studies. The selection of studies is described in the PRISMA flowchart (Figure 1) and characteristics of included studies is tabulated in Table 1.…”
Section: Re Sultsmentioning
confidence: 99%
“…After full-text scrutiny with inclusion and exclusion criteria, 37 studies were selected for qualitative synthesis. [22][23][24] As 4 studies did not provide SDs for EQ-5D scores 43,44,64,67 and 2 studies did not provide the EQ-5D score, 46,66 the meta-analysis was performed with 31 studies. The selection of studies is described in the PRISMA flowchart (Figure 1) and characteristics of included studies is tabulated in Table 1.…”
Section: Re Sultsmentioning
confidence: 99%
“…Previous studies have investigated outcomes of performing cervical spine fusions on the upper cervical spine on patients with RA. These have demonstrated that there are clear quality of life improvements seen with these procedures,[ 15 ] and outcomes depend on severity of condition at initial presentation. [ 10 ] Patients with less preoperative impairment generally have better surgical outcomes,[ 27 ] thus intervening early and before BI occurs has been shown to reduce the risk of complications and increase long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 10 ] Surgical reconstruction has been demonstrated to improve patients’ health-related quality of life, but how these medications may affect outcomes has not been investigated. [ 15 ] Our study aims to be the first to investigate how RA medications including corticosteroids, methotrexate, and biologics may affect clinical and radiological outcomes following fusions at the CVJ in the rheumatoid spine.…”
Section: Introductionmentioning
confidence: 99%
“…The mean score for this group was 21.0 (SD, 12.9), which is considered by the original authors to be in the ''moderate disability'' category [15][16][17][18][19][20][21][22][23][24]. Because this is a diseasespecific outcome measure, there is no general population standard.…”
Section: Comparisons With Other Populationsmentioning
confidence: 99%
“…Our understanding of patient QOL after spine surgery is improving [14][15][16][17][18][19][20][21][22][23][24][25], but relatively little has been published on QOL after en bloc resection of spine tumors [26][27][28]. In this study, we seek to augment the current understanding of QOL after en bloc resection of malignant spine tumors by comparing our en bloc surgery group with an internal control group who had similar disease and comorbidity status but received definitive radiation alone without major surgery.…”
Section: Introductionmentioning
confidence: 99%